2019
DOI: 10.1002/ajmg.a.61385
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral characterization of dup15q syndrome: Toward meaningful endpoints for clinical trials

Abstract: Duplication of 15q11.2-q13.1 (dup15q syndrome) is one of the most common copy number variations associated with autism spectrum disorders (ASD) and intellectual disability (ID). As with many neurogenetic conditions, accurate behavioral assessment is challenging due to the level of impairment and heterogeneity across individuals. Largescale phenotyping studies are necessary to inform future clinical trials in this and similar ID syndromes. This study assessed developmental and behavioral characteristics in a la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 44 publications
0
23
0
Order By: Relevance
“…Based on direct assessments using the Autism Diagnostic Observation Schedule (ADOS), obtained from a prior study [ 56 ], or on clinical reports of previously conducted assessments, all 15 Dup15q syndrome participants in this study met criteria for ASD. The NT control group included children that were admitted to UCLA for EEG evaluation of paroxysmal events or spells that were ultimately determined to be non-epileptic in the context of normal EEG results.…”
Section: Methodsmentioning
confidence: 99%
“…Based on direct assessments using the Autism Diagnostic Observation Schedule (ADOS), obtained from a prior study [ 56 ], or on clinical reports of previously conducted assessments, all 15 Dup15q syndrome participants in this study met criteria for ASD. The NT control group included children that were admitted to UCLA for EEG evaluation of paroxysmal events or spells that were ultimately determined to be non-epileptic in the context of normal EEG results.…”
Section: Methodsmentioning
confidence: 99%
“…Cognitive ability. All children with idic (15) and most children with int ( 15) have intellectual impairment, ranging from mild to profound (Ageeli et al, 2014;Battaglia et al, 2010;DiStefano et al, 2016DiStefano et al, , 2019Urraca et al, 2013). Individuals with dup15q syndrome show a generally consistent profile of impairment across domains, with no clear pattern of strengths and weaknesses (DiStefano et al, 2016(DiStefano et al, , 2019.…”
Section: Behavioral Phenotypementioning
confidence: 99%
“…Epilepsy is associated with a higher degree of cognitive and language impairment (DiStefano et al, 2016(DiStefano et al, , 2019. Severity of epilepsy also may relate to severity of neurodevelopmental disabilities, as evidenced by the fact that children with a history of infantile spasms have the greatest degree of cognitive impairment (DiStefano et al, 2019).…”
Section: Comorbidities: Epilepsymentioning
confidence: 99%
“…Approximately 30% of individuals with FXS (Richards et al, 2015), 26.7% with PWS (Bennett et al, 2015), and 34% with AS (Richards et al, 2015) are reported to meet diagnostic criteria for ASD. Compared to other copy number variants known to cause ASD, Dup15q syndrome confers the greatest risk (Moreno- De-Luca et al, 2013), and as such most individuals with Dup15q syndrome meet diagnostic criteria for ASD (DiStefano et al, 2020). Nonetheless, across all four syndromes autistic features are common, regardless of whether these symptoms meet diagnostic thresholds.…”
Section: Introductionmentioning
confidence: 99%